OPTIMALISASI AVAILABILITY FORKLIFT KOMATSU FD25C-17 SN: FA15 MELALUI PENDEKATAN ANALISIS RELIABILITY - Rahman, Faisal; Herlina, Firda; Trianiza, Ice; Arief, Saifullah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Muhammadiyah Gombong, 2025)
Forklifts are vital assets in industrial logistics systems, especially in material handling and loading and unloading activities in Warehouse and Jetty areas. High availability is an essential factor to ensure smooth operations and supply chain efficiency. This study aims to analyze the 2014 Komatsu FD25C-17 SN: FA15 forklift and determine the optimal preventive maintenance interval to maximize equipment availability. The research method employs an acoustic analysis approach, utilizing historical maintenance data from the period 1 January 2025 to 30 June 2025. The data is used to calculate the Mean Time Between Failures, Mean Time To Repair, and actual availability. A goodness-of-fit test is carried out to determine the best distribution probability, and the results show that the lognormal distribution best fits the smallest Anderson-Darling value (2.055 and 1.713). Based on the lognormal distribution parameters, a preventive maintenance interval simulation was conducted to find the optimal point (Topt), considering a minimum reliability of 49% and a maximum downtime of 18 hours. The simulation results show that the optimal maintenance interval was achieved at 224 hours of operation, with an availability value increasing from 89.71% to 92.32%. Although there was a slight decrease in the reliability value from 49.42% to 49.15%, this value was still within acceptable limits. This study concludes that implementing the Reliability-Centered Maintenance approach, based on lognormal distribution analysis, significantly increased forklift sales and availability. It can serve as a practical reference for making data-based maintenance policy decisions in the logistics industry.